Provokasi dan Penyesatan Terhadap Pemulasaraan Jenazah Covid-19 - Sylvana, Yana; Utomo, St. Laksanto (Lex Librum : Jurnal Ilmu Hukum, 2025)
Covid-19 first appeared at the end of December 2019, which then increased its status to a pandemic. With the high number of cases of death due to being infected with the Covid-19 virus, the World Health Organization provides a protocol for the burial of Covid-19 bodies, intending to prevent and control infection of the body. Because many ordinary people do not know about the funeral process for the Covid-19 corpse, which is different from the funeral of a corpse in general, there is often hoax news circulating that the Covid-19 body can transmit the Covid-19 virus. The number of rejection of the Covid-19 body burial is one of them because of hoax news circulating in the community and provocation carried out by irresponsible people who spread the hoax news, even though in the burial of the Covid-19 body, it must use standard operating procedures must be followed by medical personnel. The research that will be utilized uses normative juridical review, namely study by examining various sources such as sources of library materials such as journals, literature, books, written documents, and multiple laws such as legal theories, legislation, doctrine, opinions of legal experts. The approach used in this research is statutory, conceptual, and analytical approaches. This research is a prescriptive-analytical which data synthesis, discussion, and conclusions are analyzed in qualitative research. In this journal, we will discuss the case of rejection of the Covid-19 body review and see from a legal perspective the perpetrators who spread hoax news to provoke the public and also spread misleading to others.